Exploration of hydrocarbon traps using two methods within the Bogatoika area of the Dnieper-Donetsk Depression ― comparison of geological results - Shadura, O.M. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2025)
The paper aims to show the efficiency of a novel estimation technique for oil and gas in reservoirs in complicate-constructed (non-anticline) traps. In contrast to traditional techniques, which require tracing two horizons to estimate a complicated trap, this one uses only one horizon that crosses the reservoir. The new technique is based on investigating seismic waves’ absorption. Absorption was found to be very sensitive to changes in the percentage of gas in the pore reservoir. As a result, the seismic spectrum is depleted of high frequencies. Therefore, absorption is an important characteristic of rocks, complementing information about their velocity and reflective properties and increasing the efficiency of geological interpretation of seismic data. For numerical characterization of a medium’s absorption properties, the coefficient of absorption, logarithmic absorption decrement, and quality of medium Q (the quality factor Q or simply Q) are utilized. Recently, the concept of Q-quality been increasingly used in foreign literature. Quality factor can be expressed through the maximum value of elastic energy Emax stored in the sample during a period of load and energy losses DE during the same period. For large values of Q, which are usually observed in practice, Q is inversely proportional to the absorption coefficient, taking into account the proportionality coefficient. As stated above, the new method uses the phenomenon of seismic waves absorbing when they cross reservoirs with hydrocarbons. The algorithm is close to the expression structure obtained by Hauge in 1981 for exploration of well materials provided that there is no interference in the medium of investigation. It allows to measure Q from surface seismic reflection data. We adapted it to continuous measurements along the trace. It also compensates for the reflectivity’s corrupting impact. The second one is presented in a good a seismo-paleo-geo-morphological (SPGM) technique. The second technique confirms that sand bodies within the Late Serpukhovian substage are the reason of anomalies appearing as a result of the seismic waves absorption research. To prove this, two structural maps were built at the base of paleo-tectonic and paleo-geo-morphological reconstructions (the SPGM technique). Their interpretation and comparison with the map derived from seismic waves’ absorption data show that the new technique can be applied while prospecting for hydrocarbon traps. It is planned to continue its approbation within other areas.